Edukasi Pijat Common Cold sebagai Upaya Peningkatan Pengetahuan Ibu Balita di Posyandu Ngudi Rahayu II Desa Luwang: Education on Common Cold Massage as an Effort to Increase Knowledge among Mothers of Toddlers at the Ngudi Rahayu II Integrated Health Post in Luwang Village - Sugiyani, Sugiyani; Putri, Noviyati Rahardjo (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The toddler period is a vulnerable time for illness, with the common cold among the most common health issues. This disease is caused by both intrinsic (e.g., immunity and nutritional status) and extrinsic (e.g., air pollution and climate change) factors. The treatment of the common cold in toddlers is generally done through pharmacological therapy, but it is often less effective due to children's difficulty in consuming medication. As an alternative, non-pharmacological therapies such as common cold massage can be used to alleviate symptoms and boost the immune system. However, many mothers in Luwang Village, Sukoharjo, are not yet familiar with this technique. Therefore, this community service activity aims to increase mothers' knowledge about common cold massage through socialization and demonstration. The method used includes three stages: preparation, implementation (socialization and demonstration using a baby mannequin), and evaluation (pre-test and post-test). The results show a significant improvement in mothers' understanding, with an average post-test score of 9.89 compared to the pre-test score of 7.28. The demonstration proved effective in enhancing mothers' knowledge and skills. Recommendations for future activities include selecting a suitable location and improving coordination with health cadres to enhance implementation effectiveness.